La Violación de Derechos Humanos de las Personas en Base a su Identidad Sexual e Identidad de Género - ALVAREZ CASTILLO, DIANA ALEXANDRA (2018)
This research work was carried out after an exhaustive analysis of the different social problems that afflict our society, in which I have focused mainly on the study of the Human Rights of people based on their sexual identity and gender identity, people to whom and identified as human beings in vulnerable condition, due to the fact that due to their sexual orientation and gender identity their rights have been pitifully violated, in different areas of our society especially labor, education and health, due to the constant violation of their rights, consequently gives rise to discrimination. In order to carry out this research I made use of the inductive, deductive, analytical, comparative and historical methods, in addition to the use of techniques such as the survey and the interview, through which I achieved the verification of the objectives and the verification of the hypothesis. It is for this reason that by identifying that these people suffer from constant violation of their rights and that in our country there is no regulatory body that regulates the protection of the rights of people based on their sexual identity and identity. gender, therefore this research work is focused on the issue and the need to make a proposal for reform, in order to establish a regulatory body that protects the human rights of people based on their sexual identity